Answer:
a. 0.379m
b.2.646 m/s
Step-by-step explanation:
Let mass of first stone=[tex]m_1[/tex]
Mass of second stone=[tex]5m_1[/tex]
Both stones are in free fall.
The first one free fall during [tex]t_1=420 ms=420\times 10^{-3}=0.42 s[/tex]
[tex]1 s=1000 ms[/tex]
The second one free fall during [tex]t_2=t_1-180 ms=0.42-0.18=0.24 s[/tex]
Both stone start motion at the same point with initial velocity=0
a.We have to find the distance between the release point and below the release point where is the center of mass of the two stones.
[tex]y=y_0+v_0t+\frac{1}{2}gt^2[/tex]
[tex]y_0=0,v_0=0[/tex]
Substitute the values
[tex]y_1=\frac{1}{2}(9.8)(0.42)^2=0.864 m[/tex]
[tex]y_2=\frac{1}{2}\times (9.8)(0.24)^2=0.282 m[/tex]
[tex]y_{com}=\frac{m_1y_1+m_2y_2}{m_1+m_2}=\frac{m_1y_1+5m_1y_2}{m_1+5m_1}=\frac{0.864+5(0.282)}{6}=0.379 m[/tex]
Hence, center of mass from the release point at distance=0.379 m
b.We have to find [tex]v_com[/tex]
[tex]v_{com}=\frac{m_1v_1+m_2v_2}{m_1+m_2}[/tex]
[tex]v_{com}=\frac{m_1v_1+5m_1v_2}{m_1+5m_1}=\frac{v_1+5v_2}{6}[/tex]
[tex]v_1=v_01+gt=0+(9.8)(0.42)=4.116 m/s[/tex]
[tex]v_2=v_02+gt=(9.8)(0.24)=2.352 m/s[/tex]
Now, [tex]v_{com}=\frac{4.116+5(2.352)}{6}=2.646 m/s[/tex]